Implementasi jumlah lubang inti sedimen separator dalam upaya mengurangi tingkat kebuntuan filter mesin Grader CAT 16M - Ismail, Nova Risdiyanto; Suprapto, Agung; Hermawan, Dadang; Suwandono, Purbo; Hutri Wicaksono, Leo (Universitas Muhammadiyah Metro, 2024)
The Cat 16M Grader is a heavy equipment that is widely used to support mining operations. The development of this heavy equipment is required to use biodesel fuel (B30). The problem with B30 fuel is oxidation which results in the formation of sediment and can cause filter clogging. Filter clogging can affect engine power and filter replacement time. From these problems, the researcher proposed to modify the number of sediment separator core holes to reduce the filter clogging rate on the Cat 16M grader. Modified number of sediment separator core holes are 40, 20 and 10 holes with 8 mm hole dimension. Data was collected experimentally by implementing the modified sediment separator core on a Cat 16M grader for 250 hours of operation. The research resulted in the number of sediment separator core holes 10 at 250 hours of operation producing the highest sediment volume of 92 ml, the filter with the lowest clogging rate and the lowest fuel pressure difference. In addition, using the number of sediment separator cores 10 at 250 hours of operation produces the highest engine power, the highest filter clogging efficiency and has a high economic value.